(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article delves into the fascinating world of phraseological units related to flora and fauna in both English and Uzbek languages. Phraseological units are fixed expressions that hold deep cultural significance, reflecting the human perception and interaction with the natural world. The study aims to compare and contrast these idiomatic expressions, providing a semantic analysis to reveal shared metaphors, meanings, and cultural associations.